Estrategias de marketing empresarial y su impacto comercial en la empresa Amibank, Quevedo 2023 - Almeida Ochoa, Nicole Karolina (2024)
The Amibank company is a banking entity with 30 years of experience, whose focus is to support the development of communities of progress through the offer of specialized financial services, promoting financial inclusion through credits granted under the methodologies of: individual credit, community banking, consumer credit, savings services and purposeful investments, although the company by 2023, its name is established, due to the unification of the financial institutions, Insotec and Banco Finca. Financial institutions are part of the personal cycle, due to modernization, and today you can manage money virtually, in which your personal financial accounts are not at risk and thus quickly get to know the banking entity to which you are interested. citizens. On the other hand, the research methodology used is a mixed approach, applying methods that allowed us to substantiate the findings of the study phenomenon, exploratory research and field research were used: primary information was collected through an online survey, aimed at users of the service system of financial companies, Quevedo canton, with the purpose of know in depth the general environment of the Amibank Company. Finally, according to the results obtained for the research, it has been proposed to know the current situation of the company Amibank, Quevedo 2023, what are the tastes and preferences of people when choosing a service company, and it is also intended to know the brand participation and positioning.